Inverse problem for the interior spectral data of the equation of hydrogen atom - Panakhov, E. S.; Sat, M. (Springer, 2013)
We consider the inverse problem for the second-order differential operators with regular singularity and show that the potential function can be uniquely determined by the set of values of eigenfunctions at a certain interior point and parts of two spectra.
Keywords: Sturm-Liouville Operator